DIGITAL TECHNOLOGIES AND THE FORMATION OF ELECTRONIC COMMERCE IN THE GLOBAL TOURISM INDUSTRY - Yuldashev Kamol Sharifovich; Davronov Istamkhuja Olimovich (TADQIQOTLAR, 2026)
Abstract. The emergence of electronic commerce became one of the defining processes in the modern transformation of the tourism industry. Between the end of the 1980s and the year 2000, the appearance of the World Wide Web and the rapid development of internet technologies gave rise to a new digital infrastructure of tourism services, within which online reservation systems, online travel agencies, search engines, price comparison services, and review platforms were successively formed. These innovations reduced the intermediary role of traditional travel agencies and shifted the booking of accommodation, of air tickets, and of tour packages into a direct online format. The present article examines, on the basis of a historical and chronological analysis, the key milestones in the formation of electronic commerce in tourism during this period, and it systematizes the main types of digital platforms that established the foundations of the contemporary online tourism market.